Specificity, Privacy, and Degeneracy in the CD4 T Cell Receptor Repertoire Following Immunization - Sun, Yuxin; Best, Katharine; Cinelli, Mattia; Heather, James M.; Reich-Zeliger, Shlomit; Shifrut, Eric; Friedman, Nir; Shawe-Taylor, John; Chain, Benny (Frontiers in Immunology, 2017)
T cells recognise antigen using a large and diverse set of antigen-specific receptors created by a complex process of imprecise somatic cell gene rearrangements. In response to antigen/receptor binding specific T cells then divide to form memory and effector populations. We apply high throughput sequencing to investigate the global changes in T cell receptor sequences following immunisation with ovalbumin and adjuvant, to understand how adaptive immunity achieves specificity. Each immunised mouse contained a predominantly private but related set of expanded CDR3β sequences. We used machine learning to identify common patterns which distinguished repertoires from mice immunised with adjuvant with and without ovalbumin. The CDR3β sequences were deconstructed into sets of overlapping contiguous amino acid triplets. The frequencies of these motifs were used to train the linear programming boosting algorithm LPBoost to classify between TCR repertoires. LPBoost could distinguish between the two classes of repertoire with accuracies above 80%, using a small subset of triplet sequences present at defined positions along the CDR3. The results suggest a model in which such motifs confer degenerate antigen specificity in the context of a highly diverse and largely private set of T cell receptors.